2013
DOI: 10.1007/s10815-013-0118-7
|View full text |Cite
|
Sign up to set email alerts
|

Association between apolipoprotein E gene polymorphism and the risk of recurrent pregnancy loss: A meta-analysis

Abstract: Purpose The association between apolipoprotein E (ApoE) gene polymorphism and the risk of recurrent pregnancy loss (RPL) remains controversial. The present meta-analysis was performed to derive a precise estimate of the relationship. Method(s) We searched the PubMed, Embase, and Web of Science data-bases for studies related to the association between the ApoE genotype and the risk of RPL. We estimated the summary odds ratio (OR) with 95% confidence interval (CI) to assess the association. Result(s) Seven studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 16 publications
2
15
0
Order By: Relevance
“…Several reports showed no influence of APOE on recurrent miscarriage risk (10)(11)(12), while others linked APOE*4 (7,9,21,22) or APOE*2 (13) alleles with a higher risk for recurrent pregnancy loss. Two meta-analyses attempted to shed light on this issue, however, they too failed to reach a full consensus (23,24). In partial agreement with our results, Collazo et al reported an increased risk in pregnancy loss for women with the APOE*2 allele and a protective effect for APOE*4 carriers when compared with their APOE*33 counterparts (25).…”
Section: Discussionsupporting
confidence: 85%
“…Several reports showed no influence of APOE on recurrent miscarriage risk (10)(11)(12), while others linked APOE*4 (7,9,21,22) or APOE*2 (13) alleles with a higher risk for recurrent pregnancy loss. Two meta-analyses attempted to shed light on this issue, however, they too failed to reach a full consensus (23,24). In partial agreement with our results, Collazo et al reported an increased risk in pregnancy loss for women with the APOE*2 allele and a protective effect for APOE*4 carriers when compared with their APOE*33 counterparts (25).…”
Section: Discussionsupporting
confidence: 85%
“…Evidence from a meta-analysis of seven studies suggested that the APOE polymorphisms were associated with the risk of psoriasis, especially E2 and E3 alleles [ 33 ]. A meta-analysis of seven studies suggested an association between APOE E4 mutation and increased risk of recurrent pregnancy loss [ 34 ]. Evidence from a meta-analysis of 6977 subjects provides evidence that APOE E2 mutation is associated with multiple sclerosis risk [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies do not report an association between 4 status and fetal loss [56][57][58]. At least five studies and one meta-analysis report a positive association between possession of the 4 allele and fetal loss [59][60][61][62][63][64][65]. Several additional studies have examined the association between 4 carrier status and a variety of pregnancyrelated conditions.…”
Section: Reproduction and Development In Apolipoprotein 4 Carriers (Tmentioning
confidence: 99%